Philosophical coaching as a pedagogical approach aims, methods, and processes - Gonzales, Edison Joseph F.
The study highlights the importance of integrating philosophical coaching into educational practices to tackle the limitations of traditional training structures in promoting critical thinking, self-awareness, and personal growth. Philosophical coaching is considered a crucial pedagogical approach that goes beyond just academic success. This study aims to address this issue by showing how philosophical coaching may be smoothly integrated into educational environments to cultivate well-rounded individuals capable of critical thinking, ethical decision-making, and self-directed learning. The study describes a comprehensive strategy that integrates qualitative research, case studies, and theoretical analysis to investigate how philosophical coaching affects college students’ learning experiences. By utilizing methods such as interviews, data is collected from educators involved in philosophical training to gain a detailed understanding of its impact on educational outcomes, personal growth, and the development of critical thinking skills. The study demonstrates the significant influence of philosophical coaching on students’ personal and intellectual growth, showcasing improvements in critical thinking, self-awareness, moral reasoning, and emotional intelligence. The results highlight how philosophical coaching enhances the appeal and reflective nature of the learning environment, hence boosting overall educational experiences. The research indicates that including philosophical coaching in the curriculum can provide students with essential skills to handle the challenges of the 21st century, promoting lifelong learning, adaptation, and ethical leadership outside the classroom.